Prostate cancer inducing secondary linitis plastica of the rectum: a rare case report and literature review - Zhang, Dongpo; Li, Jun; Sun, Tao; Zhang, Ling; Wang, Lian; Gan, Quan; Xing, Xiaoxiao; Zhang, Yong; Wang, Yue; Liao, Daixiang; Li, Junyi (Frontiers in Oncology, 2025)
BackgroundProstate cancer, the most prevalent male malignancy in Western countries, seldom presents as secondary rectal linitis plastica (RLP).Case presentationWe present an 82-year-old man with a 6-month history of altered bowel habits, narrowed stools, and mucous discharge, with absent lower urinary tract symptoms. Serum Prostate Specific Antigen (PSA) was markedly elevated (392 ng/mL). Imaging demonstrated circumferential rectal thickening and a prostatic mass invading the bladder. MRI revealed a “target sign” with associated diffusion restriction. Colonoscopy identified circumferential mucosal protrusions resembling grape-like clusters (Nice Band Imaging (NBI) International Colorectal Endoscopic (NICE) type 3). Deep biopsies confirmed prostatic adenocarcinoma (Gleason score 4 + 3 = 7).DiagnosisA multidisciplinary team confirmed the diagnosis of prostate cancer with secondary RLP.TreatmentCombination therapy (prophylactic colostomy, leuprorelin, and abiraterone) reduced PSA from 392 to 2.16 ng/mL within 8 months.ConclusionsRLP may mimic various gastrointestinal disorders clinically. Clinicians should consider RLP in elderly men presenting with gastrointestinal symptoms. Definitive diagnosis requires the integration of multi-modality imaging, endoscopy, and histopathological biopsy.